Peapod-like architectures with CuO microspheres encapsulated within MXene as a conversion electrode for lithium-ion batteries. Issue 8 (4th January 2022) - Zhu, Ningxuan; Liu, Jianpeng; Zhang, Shukang; Zhang, Li; Liu, Xiaojing; Wang, Da; Chen, Yuhui
Abstract : A peapod-like CuO/Ti3 C2 composite for use in lithium-ion batteries presented highly improved cyclability when CuO was incorporated into a MXene scaffold, demonstrating that MXene acts as a good conductive additive. Abstract : Conversion electrode materials allow lithium-ion batteries to achieve high reversible capacities but have the problem of sluggish kinetics derived from their insulating decomposition products, thus hindering their future application. Nanostructures that shorten diffusion distances do not solve the problem as the conversion reaction is always associated with the collapse of the original structure. Here, we demonstrate that MXene would be a good conductive additive for conversion electrode materials and utilize an electrode of CuO incorporated into a MXene scaffold as a model case which demonstrates highly improved cyclability with a capacity of 670 mA h g −1 at 5C after 1000 cycles.